Breain birth vs. brain death theory: an impossible symmetry - Di Pietro, Maria Luisa; Minacori, Roberta (Medicina e Morale, 1999)
In analogy with the cerebral criterion of death assessment, several authors proposed the appearance of an active nervous system to identify the beginning of human existence. That is the core of the so called brain birth theory - or "theories", since many different interpretation have been given. The article examines the different brain birth theories (Goldenring Kushner, Burgess, Jones, etc.) and critically analyses their purposes and motivations. As it is well known, the purposes are purely practical: they are intended to set bounds, within which it would be allowed to eliminate the embryo or use it experimentally, so pursuing a gradualistic defence of it. The motivations are arbitrary: the reduction of human being to his/her brain and the identification of brain with consciousness ability. The brain birth proposal, in the end, lacks the ontological and biological and wrongfully refers to a criterion of death assessment - brain death -, which means disorders and disintegration - as it also was a criterion of identification of life beginning, which means order and progression.